2019
DOI: 10.1088/1361-6463/ab0c66
|View full text |Cite
|
Sign up to set email alerts
|

Infrared studies of gas phase and surface processes of the enhancement of catalytic methane decomposition by low temperature plasma

Abstract: Catalyst enhancement by atmospheric pressure plasma is a recently emerging field of research that embodies a complex system of reactive species and how they interact with surfaces. In this work we use an atmospheric pressure plasma jet integrated with a nickel on Al2O3/SiO2 support catalyst material to decompose methane gas by partial oxidation reaction. We use Fourier-transform Infrared spectroscopy analysis of the gas phase post reaction to measure the loss of methane and the production of CO, CO2, and H2O a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Only a few mechanistic studies are available on the surface chemistry of the plasma-catalytic oxidation of CH 4 . Knoll et al investigated the POX of CH 4 by an Ar/O 2 atmospheric pressure plasma jet (APPJ) in the presence of Ni on an Al 2 O 3 /SiO 2 support using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The authors found that CO 2 formation is enhanced at higher temperatures and that CO is likely to be converted to CO 2 on the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few mechanistic studies are available on the surface chemistry of the plasma-catalytic oxidation of CH 4 . Knoll et al investigated the POX of CH 4 by an Ar/O 2 atmospheric pressure plasma jet (APPJ) in the presence of Ni on an Al 2 O 3 /SiO 2 support using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The authors found that CO 2 formation is enhanced at higher temperatures and that CO is likely to be converted to CO 2 on the catalyst surface.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that CO 2 formation is enhanced at higher temperatures and that CO is likely to be converted to CO 2 on the catalyst surface. However, they also suggested the presence of carboxylate groups or COO – , which are likely precursors to CO 2 . Zhang et al investigated the decomposition and oxidation of CH 4 exposed to a Ni catalyst on an Al 2 O 3 /SiO 2 support and an Ar or Ar/O 2 APPJ using time-resolved DRIFTS.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, the atmospheric pressure plasma jet (APPJ) might be a suitable alternative for fundamental plasma-catalysis studies as it allows decoupling the plasma and catalyst. APPJ like approaches have been explored by a few groups [14][15][16]. APPJs can operate remotely with convective transport of reactive species to the catalytic surface, which offers opportunities for tuning the reactive species fluxes and related plasma-induced effects.…”
Section: Introductionmentioning
confidence: 99%
“…[ 331 , 332 ] In addition, when the plasma and catalyst are coupled, the CO selectivity can be improved by suppressing the formation of CH n on the catalyst surface. [ 333 , 334 ] In the study, the catalyst could be placed in the plasma region (DBD) or downstream of the plasma (MW and GA) depending on the geometry of the plasma reactor, discharge pattern, plasma temperature, and thermal stability of the catalyst. [ 55 ] Placing the catalyst in the plasma region is not feasible for thermal plasmas (e.g., MW torches, RF torches, and gliding arcs) because of the high plasma temperature (thousands of °C).…”
Section: Application Of Plasma Technology For Different Ch ...mentioning
confidence: 99%